Mediterranean Perspectives: Early Spanish and Italian Contributions to the Cinema of Irregular Migration (Giordana, Marra, Soler, Uribe) - Berger, Verena; Winkler, Daniel (Cinémas)

(untitled) (Cinémas, 2012)
This article focuses on four relatively early Italian and Spanish films treating “illegal” migrations across the Mediterranean: Imanol Uribe’s Bwana (1996), Llorenç Soler’s Saïd (1998), Vincenzo Marra’s Tornando a casa (2001) and Marco Tullio Giordana’s Quando sei nato non puoi più nasconderti (2005). The analysis predominantly looks at representations of the categories “space” and “place,” which refer both to the spatial structures of the films themselves and to the ideological structures through which the clandestines migrate. The focus of this investigation concentrates on the (border) places linked to “illegal” immigration and proposes four categories through which to understand the cinematic practice of locating irregular migration.